Prevalence and prognostic impact of mitral annular disjunction in patients with STEMI – A cardiac magnetic resonance study. Issue 5 (November 2022) - Troger, Felix; Reindl, Martin; Tiller, Christina; Lechner, Ivan; Holzknecht, Magdalena; Fink, Priscilla; Poskaite, Paulina; Pamminger, Mathias; Metzler, Bernhard; Reinstadler, Sebastian; Klug, Gert; Mayr, Agnes
Abstract: Background: Mitral annular disjunction (MAD) represents the detachment of the mitral leaflet hinge-point from the ventricular myocardium. Its role in patients with ST-segment-elevation myocardial infarction (STEMI) is unknown. This study aims to investigate the prevalence of MAD by cardiac magnetic resonance imaging (CMR) in STEMI-patients and its association with serious adverse events. Methods: STEMI-patients ( n  = 621) underwent CMR 4 days [interquartile range (IQR) 2–5] after percutaneous coronary intervention. Presence and longitudinal extent of MAD were obtained in long-axis cine-images, infarct characteristics in late gadolinium enhancement-images. During a median follow-up time of 366 days (IQR 136–454), patients were observed for the occurrence of major adverse cardiac events (MACE), comprising death, myocardial reinfarction, and congestive heart failure. Results: Overall, 307 patients (49 %) had MAD. Longitudinal MAD-distance was 4.6 ± 1.7 mm and the P3-segment was affected most frequently ( n  = 262, 85 % of MAD-patients). MAD-patients had a significantly smaller infarct size, lower prevalence of microvascular obstruction, and intramyocardial hemorrhage as well as a higher ejection fraction (all p  < 0.03). During follow-up period, MACE occurred in 52 patients (8 %) and did not show significant difference between patients with and without MAD (7 % vs. 9 %, p  = 0.424). Cardiovascular death occurred significantly more often in patients without MAD ( n  = 10, 3.2 % vs. n  = 2, 0.7 %, p  = 0.021). Conclusion: MAD is a rather common finding in patients presenting with STEMI. Patients with MAD had less severe infarct characteristics, however, they were not more commonly affected by MACE. Further confirmation and longer follow-up intervals are necessary to define the exact role of MAD in STEMI patients. Graphical abstract: MAD occurred in 51 % of patients suffering ST-segment elevation myocardial infarction. Infarct parameters such as infarct size, ejection fraction, and prevalence of IMH were significantly different between these two groups, in favor of patients with disjunction. IMH, intramyocardial hemorrhage; LVMM, left ventricular myocardial mass; MAD, mitral annular disjunction; STEMI, ST-segment elevation myocardial infarction. Unlabelled Image Highlights: Mitral annular disjunction (MAD) is a common finding in ST-segment-elevation myocardial infarction patients. The P3-segment was the most frequently affected part of the mitral valve. In our study, MAD-patients presented with less severe infarctions. Major adverse cardiac events did not occur significantly more often in MAD-patients.